From deep state to Islamic State : the Arab counter-revolution an d its Jihadi legacy - Filiu, Jean-Pierre (London : Hurst & Company, 2015)
In his disturbing and timely book Jean-Pierre Filiu lays bare the st rategies and tactics employed by the Middle Eastern autocracies, above all those of Syria, Egypt, Yemen and Algeria, that set out to crush the democratic uprisings of the 'Arab Revolution'. In pursuit of these goa ls they turned to the intelligence agencies and internal security arms of the 'deep state', the armed forces and to street gangs such as the S habiha to enforce their will. Alongside physical intimidation, imprison ment and murder, Arab counter- revolutionaries discredited and split th eir opponents by boosting Salafi - Jihadi groups such as Islamic State. They also released from prison hardline Islamists and secretly armed a nd funded them. The full potential of the Arab counter-revolution surpr ised most observers, who thought they had seen it all from the Arab des pots: their perversity, their brutality, their voracity. But the wider world underestimated their ferocious readiness to literally burn down t heir countries in order to cling to absolute power.Bashar al-Assad clam bered to the top of this murderous class of tyrants, driving nearly hal f of the Syrian population in to exile and executing tens of thousands of his opponents. He has set a grisly precedent, one that other Arab au tocrats are sure to follow in their pursuit of absolute power.
Includes bibliographic references and index.
Keywords: Counterrevolutionaries -- Arab countries; Intelligence service -- Arab countries; Jihad; Terrorism -- Arab countries; Arab Spring, 2010-; Authoritarianism -- Arab countries -- 21st century; Islam and state -- Arab countries; Arab countries -- Politics and government -- 21st century